Functional hearing and low frequency hearing preservation after cochlear implant surgery is achievable with FLEX electrode arrays: Real world evidence from the MEHS Registry - Uwe Baumann; Tobias Weissgerber; Andreas Radeloff; Ilona Anderson; Karin A. Koinig; Magdalena Breu; Stefano Morettini; Vera Lohnherr; Joachim Müller; Daniel Polterauer-Neuling (PLoS ONE, 2026)
This study uses data from the MED-EL Hearing Solutions (MEHS) multicenter registry to examine the impact of a series of flexible lateral wall electrode arrays on postoperative low frequency hearing preservation (LFHP) of cochlear implant (CI) users. Participants were members of the MEHS registry who had received a MED-EL CI with a FLEX electrode array. LFHP was evaluated using 2 formulae: the Vienna Consensus (VC), which assesses hearing preservation at 250‒1000 Hz; and the Minimum Reporting Standards for Adult Cochlear American Academy of Otolaryngology—Head and Neck Surgery (AAO), which assesses hearing preservation at 125‒500 Hz. LFHP was assessed via air conduction preoperatively and between 6 and 36 months postoperatively. LFHP was achievable with all the FLEX arrays evaluated, regardless of length. With the VC, 60% of ears (n = 95) had complete or partial LFHP at 6‒12 months postoperatively and 68.4% (n = 19) had complete or partial LFHP at 24‒36 months postoperatively. With the AAO, 43.4% of ears (n = 83) had LFHP at 6‒12 months postoperatively and 84.2% (n = 19) had functional low frequency residual hearing at 24‒36 months postoperatively. In conclusion, implantation with FLEX electrode arrays can preserve functional low-frequency residual hearing up to three years after implantation. The MEHS multicenter registry appears to be a valuable tool for collecting large amounts of real-world data from CI users despite challenges in harvesting usable data.